Light harvesting and photoprotective states in the marine diatom Fragilariopsis sp.: functional implications of chlorophylls c 1/c 2 in the fucoxanthin-chlorophyll a/c-binding proteins (FCPs) - Andreou, Charalampos; Varotsis, Constantinos (My University, 2025)
We report pH/pD-dependent fluorescence-excitation spectra of the light-harvesting fucoxanthin-chlorophyll a/c-binding proteins (FCPs) of the marine diatom Fragilariopsis sp. There is a reversible 451 to 455 nm Soret transition accompanied by a 588 to 586 nm Qx transition of chlorophylls c 1/c 2 in the pH/pD 4.9-8 range with a pK a = 5.4. The H/D exchangeable site of the 17-acrylate group of chlorophylls c 1/c 2 was characterized and from the pH/pD sensitivity of the Soret and Qy bands we suggest that the chlorophylls c 1/c 2-acrylate-H2O moiety can act as a proton acceptor/donor site. Under high intensity light conditions, the acrylate moiety of chlorophylls c 1/c 2 becomes protonated, resembling that observes under acidic conditions. In the photoprotective state, the absorption of chlorophylls c 1/c 2 is red shifted and resembles that observed in the reversible transition from light-harvesting to energy-quenching state at acidic pH. The induced ΔpH and that created from the high intensity light, is responsible for the red-shifted chlorophylls c 1/c 2 due to the protonation of the acrylate group. We present a model that describes an open and a closed form of the protonated/deprotonated chlorophylls c 1/c 2-acrylate-H2O moiety that controls the proton loading site in the photoprotective and light harvesting state.